SINGING INNOVATION IN VARIOUS MUSICAL DISCIPLINES INNOVATION IN THE POLE STYLE: गायन विभिन्न सांगितिक विद्याओ में नवाचार ध्रुवपद शैली मे नवाचार - Tripathi, Aastha (International Journal of Research -GRANTHAALAYAH, 2015)
Before the establishment of Muslim power in India, the same musical method was in the publicity. Throughout India, there was management, the Indian social life, cultural identity remained around the arrangements of daily activities, etc., due to assimilation of almost all the folk life, Indian music also adopted the external cultures and attracted them to attract The center also remained. भारत मे मुस्लिम सत्ता स्थापित होने के पहले एक ही संगीत पदधति प्रचार में थी । पूरे भारत वर्ष में प्रबन्धगान ही था, भारतीय सामाजिक जीवन, सांस्कृतिक पहचान दैनिक क्रियाकलाप आदि प्रबंधों के इर्द गिर्द ही बने रहे ,प्रायःसभी लोकजीवन को अपने में आत्मसात कर लेने के कारण भारतीय संगीत ने बाहरी संस्कृतियो को भी अपना लिया तथा उनके लिये आकर्ष ण का केन्द्र भी बना रहा ।